A Rare Primary Tumor of the Thyroid Gland: A New Case of Leiomyoma and Literature Review. (November 2018) - Zhang, Yanling; Tang, Heng; Hu, Huaiyuan; Yong, Xiang
Primary leiomyomas of the thyroid are very rare. We here report a case of a 53-year-old woman with a painless mass at the right thyroid, revealed by physical examination. The patient underwent a lobectomy. Frozen sections showed a spindle cell tumor of the thyroid gland. The nuclei of some of the tumor cells were obviously enlarged and deeply stained. Pseudocapsule invasion was observed in small foci. Samples showed neither mitosis nor necrosis and the nature of the tumor was difficult to determine. Paraffin sections showed a well-circumscribed nodular composed of intersecting fascicles of spindled to slightly epithelioid cells with eosinophilic cytoplasm and blunt-ended, cigar-shaped nuclei. We observed no significant nuclear atypia, mitotsis, or necrosis. Immunohistochemical staining showed the tumor cells to be positive for α-smooth muscle actin and h-caldesmon but negative for TG, TTF1, PAX8, S-100, CT, CK, and CD34. The ki-67 index was very low (<1%). Primary thyroid leiomyoma is rare and difficult to diagnose using frozen sections. Diagnosis requires immunohistochemical staining. Leiomyoma may be mistaken for other thyroid tumors also characterized by spindle cells.